Determination of apparent and composite friction factors for flooded equatorial natural rivers - Law, Puong Ling; Lai, Sai Hin; Mah, Darrien Yau Seng; Nabil, Bessaih; Aminuddin, Ab Ghani (Taylor and Francis Ltd., 2008)
This paper presents results, calculated from field measurements taken in several frequently flooded natural rivers, which include D and R relationships, variation of flow resistance with depth of flow, the apparent friction factor, and the composite friction factor for flooded natural rivers. The results obtained have shown the complexity of flow resistance in natural rivers due to the interaction between the main channel and floodplain flow. The interaction has given rise to a pair of apparent shear stresses at the interface region, which can significantly reduce the discharge capacity of the rivers. The apparent shear was quantified in terms of an apparent friction factor, fa, and it was found that the apparent shear stress is many times greater than the averaged boundary shear stress of the rivers. Based on the averaged boundary shear stress and apparent shear stress, the composite (actual) friction factor for the rivers can be estimated accurately (R2 = 0.99) using a statistical method that had been derived.